False Hadith, Identity, and Contestation of Thought: The Analysis of hadith on the division of Muhammad's Ummah in the Historical Dimension - Miski, Miski (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2021)
This study positioning false hadiths (mawdhû‘) as historical documents and historical data, not just past information, which is considered wrong and must be avoided. The hadith used as the object of study was the Prophet's words,